Developing Environmental Awareness among Elementary Students through Digital Media, Experiential Learning, and Local Eco-Literacy Practices - Rani Darojah; Faoyan Agus Furyanto (CENDEKIAWAN, 2026)
Eco-literacy is essential in elementary education because early environmental awareness can shape children’s values, habits, and responsible behavior toward nature. This study aims to examine how eco-literacy can be introduced to elementary students through digital media, especially YouTube, combined with storytelling, field trips, and practical environmental activities. Using a qualitative exploratory design, this study integrated a literature review and semi-structured teacher interviews to explore learning strategies, student responses, classroom implementation, and challenges in eco-literacy education. The findings show that YouTube videos increased students’ attention, curiosity, and participation by presenting environmental problems through concrete audiovisual examples. Storytelling helped students develop empathy toward nature, while field trips and outdoor activities made environmental concepts more observable and meaningful. The 5R approach (refuse, reduce, reuse, recycle, and rot) supported practical habit formation through simple classroom and school-based activities. However, the results also indicate that digital media must be carefully curated and guided by teachers to ensure accuracy, age appropriateness, and pedagogical relevance. This study concludes that eco-literacy learning is most effective when digital media are integrated with experiential learning, teacher guidance, family support, and community participation. The study contributes a contextual model for introducing eco-literacy to elementary students in the Society 5.0 era.